Impact of abandoned land on environmental protection, landscape and economic benefit in Lithuania - Gaudėšius, Rimvydas; Gurskienė, Virginija; Maliene, Vida (International Conference “Environmental Engineering”, 2017)
Human economic activity is defined as an anthropogenic process that has a negative impact on natural environment. The urbanisation and agricultural development influence the environment mostly. In order to receive economic benefit to the above-mentioned activities, the landscape is changed, the soil is affected and pollutants are released into the environment. In the light of the fact that the identified processes and problems caused by them are global, the variety of international directives are designed to minimise the impact of anthropogenic activities on the environment. The territory of the Republic of Lithuania has a considerable amount of areas, where the economic activity is suspended, i.e. the land is abandoned. This is due to a variety of social, natural and economic reasons. This process can be perceived as opposite to the anthropogenic activity, however it is important to examine how it affects the environment, landscape or economic needs. These processes are relevant on the local and international level, therefore, the scientific results of this article may be useful for the professionals in various areas and further research. The research investigates the territory of abandoned agricultural land, which is to be urbanised in the future. Land cadastre data, spatial planning documents are analysed, a questionnaire-based survey is conducted, and the actual inspection in the area is carried out. The research results identify the causes for nonuse of the land, and the impact of no economic activity on the environment, the landscape and the economic performance. To reach the set objectives, the data analysis, synthesis, induction methods have been used.